204 IDIOPATHIC POST-OPERATIVE BILATERAL VOCAL CORD PARALYSIS CAUSING ACUTE RESPIRATORY FAILURE. (1st January 2005) - Adams, A.; Serio, K. J.
Abstract : An 86 year-old male was admitted to the neurosurgery service for elective lumbar laminectomy to correct a foot drop that had been present for 18 months. Pre-operatively, the patient was found to have a normal cardiac evaluation with MIBI and normal pulmonary function tests (consisting of spirometry). His operative procedure was uneventful, and post-operatively he was admitted to the ward. He subsequently developed confusion, dyspnea, difficulty clearing copious amounts of secretions, and increasing oxygen requirements that resulted in transfer to the medical ICU. The presumptive diagnosis at that time was an aspiration pneumonia with possible swallowing dysfunction and the patient was kept NPO and treated with antibiotics and frequent naso-tracheal suctioning. On ICU day 2, the patient manifested respiratory deterioration with inspiratory stridor. Racemic epinepherine was administered acutely with minimal benefit. He then underwent bronchoscopic evaluation with intubation, which demonstrated bilateral vocal cord paralysis. He was evaluated by the ENT service who performed direct laryngoscopy in the operating room, where it was felt that his vocal cord paralysis was manageable without further intervention. At that time, the endotracheal tube was removed and he was returned to the ICU for monitoring. That evening, the patient again manifested recurrent loud stridor with increased oxygen requirements. He was given glycopyrrolate to aid in reducing secretions and was returned to the operating room on the following day to undergo percutaneous tracheostomy. The remainder of his hospital course was uneventful, consisting primarily of physical, occupational, and speech therapy for rehabilitation. We discuss the incidence, diagnosis, surgical and non-surgical management, and prognosis of vocal cord paralysis. (This abstract is being submitted through the California Thoracic Society.)